(untitled) (Revista Lusófona de Educação, 2021)
The changes that have occurred in higher education and labour market in recent years highlight the need for an in-depth reflection on current prevailing educational paradigms, and their adequacy in responding to the demands of today’s society. One of the topics that has gained particular attention is related with graduates’ employment rates, which represents one current criteria used to assess the quality of higher education institutions and courses. In this context, this article aims to reflect on current knowledge about graduates’ employability. Considering various empirical works and research lines developed over recent years, we propose a set of four premises in an effort to lend structure to some pedagogical and curricular implications for higher education institutions: (i) the risk of the “one-dimensional prioritisation” of technical skills; (ii) career management skills as a catalyst for employability; (iii) graduates and their transformative potential within organizations; (iv) the implausibility of a single model for promoting employability. To conclude, it is argued that the education of future graduates should not limit itself to the present. Pedagogical practices of teaching and learning must promote the continued construction of knowledge and skills, practical experience and work placements in organizations with different structures within the community. Keywords: higher education; graduates; employability; pedagogical implications